Molecular Mechanisms of Receptor-Mediated Endocytosis in the Renal Proximal Tubular Epithelium. (22nd November 2009) - Saito, Akihiko; Sato, Hiroyoshi; Iino, Noriaki; Takeda, Tetsuro
Abstract : Receptor-mediated endocytosis is a pivotal function of renal proximal tubule epithelial cells (PTECs) to reabsorb and metabolize substantial amounts of proteins and other substances in glomerular filtrates. The function accounts for the conservation of nutrients, including carrier-bound vitamins and trace elements, filtered by glomeruli. Impairment of the process results in a loss of such substances and development of proteinuria, an important clinical sign of kidney disease and a risk marker for cardiovascular disease. Megalin is a multiligand endocytic receptor expressed at clathrin-coated pits of PTEC, playing a central role in the process. Megalin cooperates with various membrane molecules and interacts with many intracellular adaptor proteins for endocytic trafficking. Megalin is also involved in signaling pathways in the cells. Megalin-mediated endocytic overload leads to damage of PTEC. Further studies are needed to elucidate the mechanism of megalin-mediated endocytosis and develop strategies for preventing the damage of PTEC.